Transmisión altomedieval de una receta ad uermes in homine aut in caballo - Santamaría Hernández, María Teresa (2016)
In this article we analyze the transmission of a prescription ad uermes in homine aut in caballo in three medicinal compilations from Early Middle Ages. So far the prescription has only been found in one of them, the Receptarium Laureshamense. This analysis and the comparison of the chapters that provide the prescription appear to allow us to interpret the disease for which it is indicated (uermes), which falls within the scope of Veterinary Medicine and has nothing to do with the lumbrici. In addition, we provide new data for a possible identification of the plant that is used in the prescription, called cromella.
Dans cet article, on analyse la transmission d’une prescription ad uermes in homine aut in caballo dans trois compilations médicinales du Haut Moyen Âge. Jusqu’à présent, la prescription a été localisée exclusivement dans l’un d’entre eux, le Receptarium Laureshamense. Cette analyse et la comparaison des chapitres qui fournissent la prescription permettent l’interprétation de la maladie pour laquelle elle est indiquée (uermes), qui s’inscrit dans le cadre de la Médecine Vétérinaire et n’a rien à voir avec les lumbrici. En outre, on fournit de nouvelles données pour l’identification possible de la plante utilisée dans la prescription, appelée cromella.
Keywords: Medicina